Integrating Frailty Research into the Medical Specialties—Report from a U13 Conference. Issue 10 (19th April 2017) - Walston, Jeremy; Robinson, Thomas N.; Zieman, Susan; McFarland, Frances; Carpenter, Christopher R.; Althoff, Keri N.; Andrew, Melissa K.; Blaum, Caroline S.; Brown, Patrick J.; Buta, Brian; Ely, E. Wesley; Ferrucci, Luigi; et al.
Abstract : Although the field of frailty research has expanded rapidly, it is still a nascent concept within the clinical specialties. Frailty, conceptualized as greater vulnerability to stressors because of significant depletion of physiological reserves, predicts poorer outcomes in several medical specialties, including cardiology, human immunodeficiency virus care, and nephrology, and in the behavioral and social sciences. Lack of a consensus definition, proliferation of measurement tools, inadequate understanding of the biology of frailty, and lack of validated clinical algorithms for frail individuals hinders incorporation of frailty assessment and frailty research into the specialties. In 2015, the American Geriatrics Society, the National Institute on Aging (NIA), and the Alliance for Academic Internal Medicine held a conference for awardees of the NIA‐sponsored Grants for Early Medical/Surgical Specialists Transition into Aging Research program to review the current state of knowledge regarding frailty in the subspecialties and to highlight examples of integrating frailty research into the medical specialties. Research questions to advance frailty research into specialty medicine are proposed.